2013
DOI: 10.1117/12.2024254
|View full text |Cite
|
Sign up to set email alerts
|

Optical tweezers for precise control of micro-bubble arrays: in situ temperature measurement

Abstract: We use highly a focused laser beam incident on a carbon coated coverslip to create microcavitation. Full optical control of the radii of the bubbles is attained. Multiple bubbles can also be created and their size changed independently. The dynamics of such multi-bubble systems are studied. These bubble systems generate strong flows such as Marangoni convection and also large thermal gradients. Since the size of the micro-bubbles is highly dependent on the temperature, we anticipate that these systems can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It has also been reported that by combining a confocal microscope and an optical trap, when using independent laser sources that share the same immersion objective, the change in the optical trap laser power changes the confocal focus position [23,24]. The variation in the beam convergence geometry has been considered as an effect on fluid pressure [25], as well as a change in the quantum state of the matter and radiation [13], and even the thermal effects of this convergence that are induced by modulation in radiation power have been characterized [26]. However, to the knowledge of the authors of this work, no reports have been found in the literature that suggest a change in the laser beam power of an optical trap generates any change in the phase of the wavefronts that are transmitted by the optical elements of the same trap.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that by combining a confocal microscope and an optical trap, when using independent laser sources that share the same immersion objective, the change in the optical trap laser power changes the confocal focus position [23,24]. The variation in the beam convergence geometry has been considered as an effect on fluid pressure [25], as well as a change in the quantum state of the matter and radiation [13], and even the thermal effects of this convergence that are induced by modulation in radiation power have been characterized [26]. However, to the knowledge of the authors of this work, no reports have been found in the literature that suggest a change in the laser beam power of an optical trap generates any change in the phase of the wavefronts that are transmitted by the optical elements of the same trap.…”
Section: Introductionmentioning
confidence: 99%
“…Bubble generation phenomena are frequently reported under irradiation of a focused cw laser into photoabsorbers. [6][7][8][9][10][11][12][13] A single vapor microbubble is generated at the focus, and nanometer-size objects are attracted to the bubble by the fluidic force. Based on these characteristics, cw-laserinduced bubble generation has been applied to the manipulation of DNA, 6) crystallization of glycine, 7) and patterning of quantum dots, 8) carbon nanotubes, 9) and microparticles.…”
mentioning
confidence: 99%
“…5). In conventional experiments on cw laser-induced bubble generation, [6][7][8][9][10][11][12][13] one bubble is formed at the focus, where the temperature is increased to over the boiling point of the solvent through efficient photothermal conversion. Namely, a vapor bubble is formed through a liquid=gas phase transition.…”
mentioning
confidence: 99%